PENGARUH BAURAN PEMASARAN (MARKETING MIX) TERHADAP KEPUTUSAN TAMU MENGINAP DI CRYSTAL KUTA HOTEL - Ayu Pebriyanti, Ni Kadek; Bayu Wisnawa, I Made (Jurnal Analisis Pariwisata; Vol 19 No 01 (2019): Jurnal Analisis Pariwisata (2019), 2021)
This study aims to determine the effect of the marketing mix on the decision of guests to stay at Crystal Kuta Hotel. This study uses a purposive sampling technique with a total of 110 respondents. The data used are primary data in the form of questionnaires that have been tested through an instrument test in the form of validity and reliability tests, then the data are analyzed using the classical assumption test as a prerequisite for regression tests and hypotheses using multiple linear regression analysis. The hypothesis test results state that partially the product, price, place and promotion variables have a significant effect on the guest decision to stay at Crystal Kuta Hotel, this is indicated by the product variable regression value (X1) of 0.283 with sig 0,000. Place (X3) of 0.229 with sig 0,000 and promotion (X4) of 0.160 with sig 0.002. While the price variable regression coefficient (X2) is negative at -0.103 with sig 0,000. Simultaneously the marketing mix influences the guest decision to stay at Crystal Kuta Hotel, this is indicated by the sig F value of 0,000 <0,05. Adjusted R Square value of 0.575 means that the guest decision to stay at Crystal Kuta Hotel is influenced by the marketing mix of 57.5% while the remaining 42.5% is influenced by other variables outside of this study. Based on these results, it can be seen that the most dominant variable affecting the decision of staying guests is the product variable, this is indicated by the regression coefficient of 0.283. Keywords: Marketing Mix, Product, Price, Place, Promotion, Decision of guests to stay.